Brucellosis in Iraq: epidemiology, present status, and challenges in controlling the disease - Salih, Harith Mohammed Saleem (Kansas State University, 2010)
Brucellosis is one of the major endemic zoonotic diseases worldwide, and it has history dating back to 1937 in Iraq when it was first isolated by an Iraqi physician. In order to establish a solution for the continuous devastating impacts of the disease in humans and livestock, the Brucellosis Control Program was established in 1995. The main responsibilities of this program were setting and implementing the appropriate strategies for controlling the disease. After the war in 2003, the United Nation organization for Food and Agriculture (FAO) developed a strategic plan to control the disease. The main goal of the project was to improve productivity in the livestock sector and reduce the prevalence of disease in small ruminants (sheep and goats) to less than 2%, and less than 0.2% in cattle and buffalo. Achieving such goals ultimately would reduce the disease incidence among the human population from more than 27.2 cases/100,000 persons in 2002, to less than 4 cases/100,000 people within 15 years. A serological surveillance was conducted and revealed the apparent prevalence of the disease in sheep and goats, cattle, buffalo, and camels was 6.51%, 1%, 1.48%, and 0.02%, respectively in Iraqi governorates except the three northern governorates of Kurdistan province . Based on surveillance results, a vaccination policy was the only appropriate strategy that could be chosen to control the disease. Four vaccination campaigns were implemented in 2006, 2007, 2008, and 2009, with a total number of vaccinated animals each year at 10099972, 4698482, 753153, and 1833482 head, respectively. The primary satisfactory outcome of the program was the apparent decline in livestock abortions leading to obvious increases in productivity. Regarding the incidence of brucellosis among the human population, the apparent decline in the middle and south of Iraq began with the vaccination phase of the control program in 2006. The results represented a significant decrease in human cases after only four vaccination campaigns of a program that was intended to continue for 15 years.
Keywords: Brucellosis; Iraq; Biology, Microbiology (0410); Biology, Veterinary Science (0778); Health Sciences, Public Health (0573)